Front Cover: Bioinspired Oxidative Cleavage of Aliphatic C–C Bonds Utilizing Aerial Oxygen by Nickel Acireductone Dioxygenase Mimics (Eur. J. Inorg. Chem. 16/2019). Issue 16 (17th April 2019) - Raje, Sakthi; Mani, Kalaikodikumaran; Kandasamy, Parameswaran; Butcher, Ray J.; Angamuthu, Raja
Abstract : The Front Cover shows the oxidative cleavage of aliphatic C–C bonds of the acireductone model substrate bound to the nickel(II) center. The scissors point to the C–C bonds that are cleaved. The background symbolizes the utilization of aerial oxygen by nickel acireductone dioxygenase mimics to cleave the C–C bonds. More information can be found in theCommunication by R. Angamuthu et al. For more on the story behind the cover research, see theCover Profile .